2016
DOI: 10.1093/gbe/evw046
|View full text |Cite
|
Sign up to set email alerts
|

Localizing Ashkenazic Jews to Primeval Villages in the Ancient Iranian Lands of Ashkenaz

Abstract: The Yiddish language is over 1,000 years old and incorporates German, Slavic, and Hebrew elements. The prevalent view claims Yiddish has a German origin, whereas the opposing view posits a Slavic origin with strong Iranian and weak Turkic substrata. One of the major difficulties in deciding between these hypotheses is the unknown geographical origin of Yiddish speaking Ashkenazic Jews (AJs). An analysis of 393 Ashkenazic, Iranian, and mountain Jews and over 600 non-Jewish genomes demonstrated that Greeks, Roma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(81 citation statements)
references
References 73 publications
1
79
0
1
Order By: Relevance
“…Following its destruction, these people migrated to Eastern and Northern Europe and bolstered the Ashkenazic Jewry communities. Das et al (2016) showed that Ashkenazic Jews trace their origins to "Ancient Ashkenazic," South to the Black Sea. From there, Jews could have penetrated Europe from two directions: through Western Turkey or by crossing Khazaria and entering from Eastern Europe after the demise of the Empire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following its destruction, these people migrated to Eastern and Northern Europe and bolstered the Ashkenazic Jewry communities. Das et al (2016) showed that Ashkenazic Jews trace their origins to "Ancient Ashkenazic," South to the Black Sea. From there, Jews could have penetrated Europe from two directions: through Western Turkey or by crossing Khazaria and entering from Eastern Europe after the demise of the Empire.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, the Caucasus Jews included in the original dataset were omitted from this study. This choice of a limited and irrelevant dataset to address a key question in the manuscript is peculiar provided the numerous datasets (e.g., Need et al 2009;Bray et al 2010;Das et al 2016;Gladstein and Hammer 2016) which, unlike the so-called "Jewish HapMap Project," do not require signing a contract that limits the academic freedom of the authors. Using a small dataset is bound to produce limited results, which may lead one to conclude that "the genetic homogeneity of the worldwide Jewish population is also problematic.…”
Section: Choice Of the Reference Datasetmentioning
confidence: 99%
“…Thus far, all analyses aimed to geo-localize AJs (Behar et al, 2013, Figure 2B; Elhaik, 2013, Figure 4; Das et al, 2016, Figure 4) identified Turkey as the predominant origin of AJs, although they used different approaches and datasets, in support of the Irano-Turko-Slavic hypothesis (Figure 1A, Table 1). The existence of both major Southern European and Near Eastern ancestries in AJ genomes are also strong indictors of the Irano-Turko-Slavic hypothesis provided the Greco-Roman history of the region southern to the Black Sea (Baron, 1937; Kraemer, 2010).…”
Section: The Genetic Structure Of Ashkenazic Jewsmentioning
confidence: 97%
“…The existence of conflicting reports has led to debates about their veracity and authenticity; even the very practice of Judaism by the Khazars has been questioned [7]. Yet, recent work on geographical genetics and linguistics of present-day Ashkenazi populations lent support to the hypothesis of the Khazarian origin [8][9][10]. However, the methodology of this work has been subjected to critique, citing the difficulty of reconstructing ancestral Jewish populations without appropriate Khazarian proxies in using present-day data.…”
Section: Introductionmentioning
confidence: 96%